PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX DAN PROFITABILITAS PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Cahyaningtyas, Arfianty Reka; Hadiprajitno, P. Basuki (Diponegoro Journal of Accounting, 2015)
This  study  aims  to  provide  empirical  evidence  about  relationship  between  Corporate Governance Perception Index and profitability which is measured by Return on Asset towards corporate value which is measured by Tobin’s Q.The object of this study are companies listed on the Corporate Governance Perception Index in 2011-2013 which is assessed by The Indonesian Institute of Corporate Governance, an independent institute that conducting dissemination and development of Good Corporate Governance in Indonesia. The sampling method is purposive sampling that based on criterion which has been determined before. Hypotheses in this study are tested by descriptive statistic and multiple regression analysis method.The results of statistical test (F Test) shows that all independent variables affect corporate value. The effect of independent variable Corporate Governance Perception Index towards corporate  value  on  the  T  test  is  not  significant.  While  profitability  has  significant  effect  to corporate value.